The Clinical Characteristics and Outcomes of Adult Patients With Pneumonia Related to Three Paramyxoviruses - Chen, Liang; Han, Xiudi; Li, YanLi; Zhang, Chunxiao; Xing, Xiqian (Frontiers in Medicine, 2021)
Background: Respiratory syncytial virus (RSV), human metapneumovirus (hMPV) and human parainfluenza virus (hPIV) are paramyxoviruses that are important etiologies of community-acquired pneumonia. However, current knowledge about the clinical features and outcomes of paramyxovirus-related pneumonia (PMV-p) is limited. We aimed to investigate the clinical characteristics and disease severity in immunocompetent, adults hospitalized with hMPV (hMPV-p) and hPIV-related pneumonia (hPIV-p) with RSV-related pneumonia (RSV-p). Methods: We retrospectively recruited 488 patients with PMV-p (153 with RSV-p, 137 with hMPV-p and 198 with hPIV-p) from five teaching hospitals in China during 2011 to 2019. Univariate and multivariate analysis were performed to identify predictors to distinguish hMPV-p/hPIV-p from RSV-p, and evaluate the effects of virus types on the clinical outcomes. Results: Compared with RSV-p, sputum production [odds ratio (OR) 5.029, 95% confidence interval (CI) 2.452 - 10.312, P < 0.001] was positively associated with hMPV-p, while solid malignant tumor (OR 0.346, 95% CI 0.126 - 0.945, P = 0.038), nasal congestion (OR 0.102, 95% CI 0.041 - 0.251, P < 0.001) and respiratory rate ≥ 30 breaths/min (OR 0.296, 95% CI 0.136 - 0.640, P = 0.002) were negatively related to hMPV-p; Sputum production (OR 13.418, 95% CI 6.769 - 26.598, P < 0.001) was positively associated with hPIV-p, while nasal congestion (OR 0.194, 95% CI 0.098 - 0.387, P < 0.001), dyspnea (OR 0.469, 95% CI 0.272 - 0.809, P < 0.001) and respiratory rate ≥ 30 breaths/min (OR 0.090, 95% CI 0.032 - 0.257, P < 0.001) on admission were negatively related to hPIV-p. After adjustment for confounders, multivariate logistic regression analysis suggested that hMPV-p (OR 0.355, 95% CI 0.135 - 0.932, P = 0.035) and hPIV-p (OR 0.311, 95% CI 0.121 - 0.784, P = 0.013) were associated with decreased 30-day mortality compared with RSV-p. RSV infection (OR 4.183, 95% CI 1.709 - 10.236, P = 0.002) was identified as an independent predictor of 30-day mortality in patients with PMV-p. Conclusion: RSV-p caused more severe disease than hMPV-p and hPIV-p. Although some clinical features are helpful for distinguishing the diseases, etiologic diagnosis is critical in the management of the PMV-p.